Learning Valuable Things from Words of Poverty in V.S. Naipauls Miguel Street - Suryo Sudiro (Universitas Sanata Dharma, 2015)
In addition to consisting of an interesting story, a novel may consist of lessons to learn. V.S. Naipauls Miguel Street reflected realities of People in Trinidad. The cynical words in the novel tell how people live in poverty. It is not only a story of past events but also a valuable text to see and learn actual realities of education. There are two lessons that readers can learn from the words. First, what adult people do are lessons for the teenagers. When the adult show bad characters teach how to do bad conducts, the teenagers will easily see and do the same things. When the adults resort to violence in their families, the teenagers will resort to the same things outside homes. When the adults drink alcohol and consume drugs, the teenagers will try and do the same, or even, worse. They will run out of their homes and find other places to live. The matters will deteriorate when the teenagers do not have proper education. It is a threat of character education. Second, there are always heroes in communities. Parents are some of them. The heroes provide poor children and teenagers with proper education. They show that there is always a valuable thing to do in poor condition. It shows that poverty does not only supply threats of character education but also opportunities of it. The schools should conduct good education. The schools should educate mind and heart.